2016
DOI: 10.1002/2016jd025605
|View full text |Cite
|
Sign up to set email alerts
|

High‐speed video observation of stepwise propagation of a natural upward positive leader

Abstract: Using a high‐speed video camera operated at 150,000 frames per second, we have documented the upward propagation of an initial positive leader from a 325 m meteorological tower in Beijing. The stepwise development of the upward positive leader was clearly revealed during its self‐sustained propagation toward the cloud base, providing the first optical evidence for the stepping processes of a positive leader. The leader developed with definitive intermittent pauses and re‐establishment with abrupt jump of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
55
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 28 publications
11
55
2
Order By: Relevance
“…In laboratory experiments, no mechanism for stepped propagation of positive leaders has been identified, unlike the finding of stepping mechanism in the propagation of negative leaders, corresponding to the instantaneous bridging of the gap between the negative tip of the leader and a plasma stem with bipolar streamers, positive streamers facing toward the leader tip, and negative streamers facing outward. This stepping mechanism in negative leaders has also been identified in nature, as reported in several works, such as those by Biagi et al (), Hill et al (), Petersen and Beasley (), Qi et al (), and Wang et al ().…”
Section: Discussion On Specific Features Of Upward Leaders In Naturalsupporting
confidence: 64%
“…In laboratory experiments, no mechanism for stepped propagation of positive leaders has been identified, unlike the finding of stepping mechanism in the propagation of negative leaders, corresponding to the instantaneous bridging of the gap between the negative tip of the leader and a plasma stem with bipolar streamers, positive streamers facing toward the leader tip, and negative streamers facing outward. This stepping mechanism in negative leaders has also been identified in nature, as reported in several works, such as those by Biagi et al (), Hill et al (), Petersen and Beasley (), Qi et al (), and Wang et al ().…”
Section: Discussion On Specific Features Of Upward Leaders In Naturalsupporting
confidence: 64%
“…It looks like a space leader inside the positive streamer zone, with its forward extending positive part being pronounced and branched and the negative part being undetectable. Alternatively, the floating formation was actually connected to the primary channel, in which case it was part of the transition from the corona streamer burst to the regular positive streamer zone. Comparison with the features of positive and negative leaders observed in lightning shows that for either polarity, the stepping in long sparks appears to be qualitatively similar to the stepping in lightning. Our results for positive‐leader stepping, together with those published by Les Renardieres Group for positive sparks and by Wang et al () for UPL in natural upward lightning, argue against the notion (e.g., Saba et al, ; Visacro et al, ) that positive leader cannot (or unlikely to) produce true steps in positive leaders, only fluctuations of current and luminosity induced by a simultaneously developing negative stepped leader.…”
Section: Discussionsupporting
confidence: 45%
“…Space stems/leaders have never been observed in positive leaders. Further, Baldo and Rea (, ) and Wang et al () reported that the positive‐leader step extended in the forward direction. On the other hand, Pilkey (, Figures A‐1 and A‐2) reported on a floating channel segment, similar to a space leader, but developing on a time scale of the order of hundreds of microseconds and making connection to the lateral surface of a cloud‐discharge channel that was inferred to be positively charged.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations